Origins of metabolic diversity: substitution of homologous sequences into genes for enzymes with different catalytic activities. - Yeh, W K (1980)
Similar amino acid sequences were found in portions of bacterial enzymes that mediate different biochemical transformations. Reaction catalyzed by the enzymes include oxygenation, decarboxylation, isomerization, and hydrolysis. The proteins share a common evolutionary history because they participate in an overall catabolic process known as the beta-ketoadipate pathway. One interpretation of the sequence similarities might be that duplication of a single gene gave rise to ancestral genes for the enzymes with different catalytic activities. According to this view, homologous sequences from the ancestral gene were conserved as the proteins diverged to assume different functions. This hypothesis is vitiated by comparison of the NH2-terminal amino acid sequences of sets of enzymes that mediate identical or analogous metabolic reactions within an organism. Gene duplications giving rise to the enzymes within each set must have followed duplication of a putative ancestral gene for all the sets. Yet the amino acid sequences of the proteins within each set have diverged widely, and against this background of divergence the conservation of sequences from an ancestor common to all the enzymes is unlikely. Rather, it appears that most regions of sequence similarity shared by enzymes from different sets were acquired subsequent to their divergence from any common ancestor. In some cases it appears that relatively short regions of sequence homology were achieved by mutations causing the transfer of sequence information from one set of structural genes to structural genes in another set. Alignment of homologous amino acid sequences within any single set requires the introduction of few gaps. Because gaps are required to align sequences that have been altered by the insertion of genetic material, the evidence indicates that copies of oligonucleotides were exchanged by genetic substitution among different structural genes as they coevolved.